Hubungan Dukungan Keluarga Dengan Frekuensi Kunjungan Lanjut Usia Ke Posyandu Lansia Di Wilayah Kerja Puskesmas Kecamatan Tahuna Barat - Gunena, Justisia; Natalia M., Adriani; Sari, Andi Buana (Program Studi Ilmu Keperawatan Fakultas Kedokteran Universitas Sam Ratulangi, 2023)
Background: The Tahuna West District Health Center found that there were still older adult who were less active, so family support was needed to encourage interest in the willingness of the older adult to participate in older adult Posyandu activities. Objective: To determine the relationship between family support and the frequency of older adult visits to Integrated Healthcare Center for the older adult in the working area of ​​the Tahuna West District Health Center. Method: Quantitative research method with an approach cross sectional. Cluster Random Sampling by involving 178 respondents. The Perceived Social Support-Family (PSS-Fa) questionnaire and the frequency of visiting the older adult can be measured by referring to the Healthy Towards Card. Results: The frequency of visiting the older adult at the Integrated Healthcare Center shows that most of the older adult have the highest maximum frequency of visits as many as 4 times present with a total of 60 people, then the lowest frequency of visits is as many as 7 times attending the older adult Integrated Healthcare Center with a total of 1 person. Based on the results of statistical (p <0.001). Conclusion: There is a relationship between family support and the frequency of older adult visits to the older adult Integrated Healthcare Center. The better the family support, the better the utilization of the older adult Integrated Healthcare Center. Keywords: older adult; older adult integrated healthcare center; family support; frequency of visits.